Respuesta :

Answer:

Lets calculate the value for each expression to get the answers

f(x) = x² + 6x + 9

g(x) = x² - 9

(f+g)(x) = x² + 6x + 9 + x² - 9

(f+g)(x) = 2x² + 6x

(f+g)(x) = 2x(x + 3)

(f-g)(x) = x² + 6x + 9 - (x² - 9)

(f-g)(x) = x² + 6x + 9 - x² + 9

(f-g)(x) = 6x + 18

(f-g)(x) = 6(x + 3)

(f×g)(x) = (x² + 6x + 9)(x² - 9)

(f×g)(x) = x⁴ - 9x² + 6x³ - 54x + 9x² - 81

(f×g)(x) = x⁴ + 6x³ - 54x - 81

(f÷g)(x) = (x² + 6x + 9) / (x² - 9)

(f÷g)(x) = (x+3)(x+3) / (x+3)(x-3)

(f÷g)(x) = (x+3)/(x-3)